2017
DOI: 10.1016/j.copbio.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Nasal chondrocytes as a neural crest-derived cell source for regenerative medicine

Abstract: Cells deriving from neural crest are generally acknowledged during embryonic development for their multipotency and plasticity, accounting for their capacity to generate various cell and tissue types even across germ layers. At least partial preservation of some of these properties in adulthood makes neural crest derived cells of large interest for regenerative purposes. Chondrocytes from fully mature nasal septum cartilage in adults are also derivatives of neural crest cells and were recently demonstrated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 54 publications
0
36
0
1
Order By: Relevance
“…Although it remains unclear whether the same cells would make durable cartilage tissue when implanted into a cartilage-inducing/maintaining environment, such as an articular cartilage defect, ex-vivo studies showed promising results [22]. Moreover, there are differences for the two investigated cell types as they have different origins during embryonic development [44]. While articular chondrocytes develop from the mesoderm, auricular chondrocytes originate from the neural crest.…”
Section: Discussionmentioning
confidence: 99%
“…Although it remains unclear whether the same cells would make durable cartilage tissue when implanted into a cartilage-inducing/maintaining environment, such as an articular cartilage defect, ex-vivo studies showed promising results [22]. Moreover, there are differences for the two investigated cell types as they have different origins during embryonic development [44]. While articular chondrocytes develop from the mesoderm, auricular chondrocytes originate from the neural crest.…”
Section: Discussionmentioning
confidence: 99%
“…Nasal chondrocytes derive from the neural crest 46 . Different investigations demonstrated that nasal chondrocytes are also able to display their effect, in particular, the synthesis of extracellular cartilage matrix, in other locations and are thus suitable as a possible cell source for transplantation 46 47 . A clinical phase I study 45 has already been conducted that confirmed these findings also in the clinical practice.…”
Section: Regenerative Medicine In Clinical Routinementioning
confidence: 99%
“…Es konnte in verschiedenen Untersuchungen gezeigt werden, dass nasale Chondrozyten auch an anderer Lokalisation wie z. B. dem Kniegelenk in der Lage sind ihre Wirkung, d. h. insbesondere die Synthese extrazellulärer Knorpelmatrix zu entfalten und somit als mögliche Zellquelle für die Transplantation geeignet sind 46 47 . Es wurde bereits eine klinische Phase I Studie 45 durchgeführt, die diese Erkenntnisse auch in der Klinik bestätigt.…”
Section: 1 üBerblickunclassified
“…They derive from the neural crest, and have been recently shown to be able to respond and adapt to heterotopic transplantation sites. In particular, chondrocytes from the nasal septum have shown improved reproducibility in generating hyaline-like cartilage tissues, with superior plasticity to adapt to a joint environment, resulting in improved tissue regeneration and repair [8][9][10].…”
Section: Introductionmentioning
confidence: 99%